2012
DOI: 10.1371/journal.pone.0031563
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Molecular Diagnostic Test in AFB Smear Positive Tuberculosis Suspects Greatly Reduces Time to Detection of Multidrug Resistant Tuberculosis

Abstract: BackgroundThe WHO has recommended the implementation of rapid diagnostic tests to detect and help combat M/XDR tuberculosis (TB). There are limited data on the performance and impact of these tests in field settings.MethodsThe performance of the commercially available Genotype MTBDRplus molecular assay was compared to conventional methods including AFB smear, culture and drug susceptibility testing (DST) using both an absolute concentration method on Löwenstein-Jensen media and broth-based method using the MGI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 16 publications
(23 reference statements)
6
74
2
1
Order By: Relevance
“…Our results are comparable with results of other investigator who found that the onset of DILI ranged from 13 days to 58 days (median, 26 days) after initiation of treatment [36]. And in another study, the median latent period for developing DILI was found to be 19 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] days [37].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results are comparable with results of other investigator who found that the onset of DILI ranged from 13 days to 58 days (median, 26 days) after initiation of treatment [36]. And in another study, the median latent period for developing DILI was found to be 19 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] days [37].…”
Section: Discussionsupporting
confidence: 88%
“…Culture was performed using solid (Lowenstein-Jensen) and liquid (MGIT BACTEC 960) media using standard methodologies [14,15].…”
Section: Methodsmentioning
confidence: 99%
“…The national surveillance study on resistance to anti-TB drugs conducted in Colombia during 2004 and 2005 showed a prevalence of MDR-TB among untreated patients of 2.38% (95% CI 1.58 -3.57) and of 50.6% among patients classified in Category I treatment failure (basic scheme for new tuberculosis patients) (21). In a recent study, a molecular test reduced MDR-TB detection time from 67.3 days (solid medium) and 21.6 days (liquid medium) to less than 5 days (4.2 days) compared to phenotypic methods (22).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to culture, all tissue samples were first homogenized with a tissue grinder before inoculation on Lowenstein-Jensen (LJ)-based solid medium. For cultures with growth of M. tuberculosis, first-and second-line DST was performed as previously described (26,27). DST for pyrazinamide was not performed.…”
Section: Methodsmentioning
confidence: 99%